Analyzing of Bank Performance and Customer Satisfaction in Commercial Bank: A Case Study on Nepal Bank Ltd. in Damauli Branch - Shrestha, Buddha Kumar (The Journal of Aadikavi, 2023)
This study undertakes a comprehensive analysis of bank performance with a primary focus on measuring customer satisfaction. This endeavor is of significant value not only to service-oriented enterprises at large but also holds particular relevance to the banking sector. A central tenet of this research is to underscore the importance of aligning customer-centric strategies with the diverse needs of customers. At its core, this study seeks to illuminate the profound impact of the service quality rendered by Nepal Bank on customer satisfaction, thereby establishing a clear linkage between the two. The research employs purposive and convenience sampling techniques within a non-probability sampling framework. Both descriptive and analytical research designs are employed to elucidate the research objectives. Data collection is accomplished through the survey method, where a meticulously designed questionnaire is disseminated among bank customers. The questionnaire encapsulates customer service parameters and financial performance considerations, along with key determinants influencing these facets. The study employs the chi-square test to test its hypotheses. Statistical analyses entail a five-point Likert scale and a diverse range of tools, including measures such as mean, standard deviation, coefficient of variation, Karl Pearson’s correlation coefficient, and regression analysis, to comprehensively evaluate the variables of interest. The findings of this study underscore the unequivocal linkage between bank performance and customer satisfaction. The study unequivocally concludes that the performance metrics of a bank wield a direct and substantial influence on customer satisfaction levels. The pivotal role of bank performance in driving customer satisfaction is a central implication of this study. Consequently, the banking industry is urged to continuously update its operational performance to be in congruence with the evolving preferences and desires of customers. In conclusion, the insights garnered from this study highlight the critical interplay between bank performance and customer satisfaction. These findings underline the crucial role of customer-centric strategies in enhancing the banking experience. The implications extend to the broader financial service industry, emphasizing the need for adaptive policies that align business operations with customer expectations.